ACEi and ARBS in Hypertension and Heart Failure - Perrone Filardi, Pasquale; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book summarizes how the renin angiotensin system is implicated in the progression of atherosclerotic disease as well as of left ventricular dysfunction and reviews the action of angiotensin converting enzyme inhibitors and AT1 receptor antagonists on reducing morbidity and mortality in patients with left ventricular dysfunction or in those at high cardiovascular risk with preserved ventricular function. ACEi and ARBS in Hypertension and Heart Failure is a highly practical reference reviewing the evidence and providing a rationale for the appropriate use of RAS antagonists in cardiovascular diseases. It is written in an easy-to-follow format and with many illustrations to aid clarity and the assimilation of information. Each chapter is written by established authorities in their fields who are also experienced in explaining often complex concepts. The result is a unique book which is not only comprehensive but also clear and useful for the busy medical practitioner.
Pathogenetic mechanisms of RAS involvement in cardiovascular diseases -- Antiotensin converting enzyme inhibitors and at1 antagonists for treatment of hypertension.- Renin angiotensin system antagonism in heart failure -- Impact of co-morbidities on RAS inhibitors choice in hypertensive and heart failure patients -- Target organ damage and RAS blockade.
Keywords: Cardiology; Pharmacotherapy; Cardiology; Pharmacotherapy